NADPH oxidase 4 has a crucial impact on the microcirculation of hypercholesteremic LDL receptor deficient mice. (14th October 2021) - Diaba-Nuhoho, P; Shahid, A; Brunssen, C; Morawietz, H; Brendel, H
Abstract: Introduction: NADPH oxidase (NOX) 4-generated H2O2 has anti-atherosclerotic properties in conduit arteries like the aorta and carotids. However, the role of NOX4 on vascular function of small resistance arteries and blood pressure in a mouse model of familial hypercholesterolemia is unknown. Purpose: We evaluated whether NOX4-generated H2O2 might play a role in perivascular adipose tissue of the thoracic aorta (tPVAT) and small resistance arteries on vascular function in a mouse model of familial hypercholesterolemia. Methods: Aortic segments and mesenteric arteries from 26-week-old Ldlr−/− and Nox4−/− / Ldlr−/− mice were analysed by Mulvany myograph. In addition, vascular contraction and relaxation was analysed in the presence of L-NAME and catalase. Analysis of mRNA expression was performed in murine and human tissue by quantitative real-time PCR. Blood pressure was detected by tail cuff method in conscious, trained mice. Results: Loss of NOX4 led to severe endothelial dysfunction in mesenteric arteries of Ldlr−/− mice. Blocking of NO synthases with L-NAME led to decreased endothelial relaxation in Ldlr−/− mice at the level of Nox4−/− / Ldlr−/− mice. However, incubation with L-NAME did not worsen the established endothelial dysfunction of the mesenteric arteries from Nox4−/− / Ldlr−/− mice. These results are strikingly different from the aorta, where inhibition of NO synthases led to a similarly impaired endothelial relaxation in both mouse strains. We detected a similar eNOS expression in the aorta of Ldlr−/− and Nox4−/− / Ldlr−/−, but a reduced eNOS expression in the mesenteric arteries of Nox4−/− / Ldlr−/− mice. H2O2 can induce eNOS expression. Therefore, we analysed the vascular function after catalase incubation and again found a significant reduction of endothelial function in the mesenteric arteries of Ldlr−/− mice. Finally, we analysed blood pressure of these mice and did not observe differences in systolic blood pressure, despite significant differences in endothelial function of resistant arteries. Conclusion: NOX4 protects against severe endothelial dysfunction in the mesenteric artery in a model of hypercholesterolemia. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Ghanaian-German postgraduate training scholarship program (DAAD)